Composite aerogel powder prepared by normal pressure method and preparation method thereof

By combining alumina sol and polyimide aerogel into the aerogel material and introducing modified carbon fibers to form composite aerogel powder, the problem of insufficient mechanical properties and high temperature resistance of existing aerogel materials is solved. , achieves efficient thermal insulation and mechanical properties improvement, and reduces production costs, making it suitable for large-scale industrial production.

CN119219972AActive Publication Date: 2024-12-31SHANDONG HUACHENG HIGH TECH ADHESIVE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411765738.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2024-12-31
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing aerogel materials have shortcomings in terms of mechanical properties and high temperature resistance, and the production costs are high, making it difficult to achieve large-scale industrial production.

Method used

Compound aerogel powder is prepared by the atmospheric pressure method. By combining the alumina sol with the polyimide aerogel, an interpenetrating network structure is formed and modified carbon fiber is introduced to improve the overall performance and stability of the material.

Benefits of technology

It significantly improves the insulation, mechanical properties and high temperature resistance of the material, is suitable for high temperature application scenarios, and uses the atmospheric pressure method to reduce production costs and equipment complexity, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of aerogel materials, in particular to composite aerogel powder prepared by a normal pressure method and a preparation method of the composite aerogel powder, which are used for solving the problems that an existing aerogel material is poor in mechanical property and high temperature resistance, relatively high in production cost and difficult to realize large-scale industrial production. The composite aerogel powder combines the advantages of aluminum oxide aerogel and polyimide aerogel, so that the two materials can support each other and bear external force together, the overall performance of the material is improved, and after the modified carbon fibers are doped into the composite aerogel powder, an interpenetrating network structure can be supported, hole shrinkage collapse and cracking are avoided, and the service life of the composite aerogel powder is prolonged. According to the preparation method, the overall stability of the material is further improved, the composite aerogel powder is endowed with excellent heat-insulating property, mechanical property and high-temperature resistance, high-temperature and high-pressure conditions required by a supercritical drying process are avoided by utilizing a normal-pressure method, and the preparation method is simple in equipment, low in cost, high in safety and beneficial to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aerogel materials, and in particular to a composite aerogel powder prepared by a normal pressure method and a preparation method thereof. Background Art

[0002] Aerogel is a new type of material with a nanoporous structure. It has excellent properties such as extremely low density, high specific surface area, and low thermal conductivity. It has broad application prospects in thermal insulation, adsorption separation, catalysis and other fields.

[0003] Most existing aerogel materials are prepared using chemical drying or supercritical drying technology. Although these methods can produce high-performance aerogels, they are usually complicated to operate and costly, making it difficult to achieve large-scale industrial production. In addition, traditional inorganic aerogels have low thermal conductivity but are relatively brittle, resulting in poor mechanical properties. Traditional organic aerogels have excellent mechanical properties but have the disadvantage of poor high temperature resistance. Therefore, single-component aerogels have different shortcomings and cannot meet practical applications, making it difficult to meet the requirements of specific application scenarios for the comprehensive performance of materials.

[0004] Therefore, developing a normal pressure method for preparing composite aerogel powder and its preparation method is of great significance for improving the mechanical properties and high temperature resistance of aerogel materials and reducing production costs. Summary of the invention

[0005] In order to overcome the above technical problems, the purpose of the present invention is to provide a composite aerogel powder prepared by a normal pressure method and a preparation method thereof, which solves the problems that the existing aerogel materials have poor mechanical properties and high temperature resistance, high production costs, and difficulty in large-scale industrial production.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A composite aerogel powder is prepared by a normal pressure method, comprising the following components in parts by weight:

[0008] 20-25 parts of 4,4'-diaminodiphenyl ether, 30-35 parts of pyromellitic anhydride, 90-100 parts of N-methylpyrrolidone, 5-7 parts of pyridine, 15-21 parts of propionic anhydride, 3-11 parts of 3-aminopropyltriethoxysilane, 6-10 parts of aluminum isopropoxide, 7-11 parts of acetic acid, 18-22 parts of deionized water and 0.5-7.5 parts of modified carbon fiber;

[0009] Wherein, the modified carbon fiber is prepared by the following steps:

[0010] Step a1: Add carbon fiber, concentrated nitric acid and concentrated sulfuric acid into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 85-90°C and continue stirring and reacting for 2-3 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with distilled water for 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 60-65°C for 2-3 hours to obtain oxidized carbon fiber;

[0011] Step a2: 3,4-dihydroxybenzaldehyde and anhydrous methanol are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, and then 1,3-diamino-2-hydroxypropane solution is added dropwise while stirring, and the dropping rate is controlled to be 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to 60-65° C. and the stirring reaction is continued for 6-8 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then poured into ice water, and then vacuum filtered. The filter cake is washed with distilled water for 3-5 times, and then placed in a vacuum drying oven, and dried at a temperature of 60-65° C. for 2-3 hours to obtain a polyhydroxy intermediate;

[0012] Step a3: Add the polyhydroxy intermediate, benzyltriethylammonium chloride and epichlorohydrin to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then heat to 90-95° C. and continue to stir and react for 6-8 hours, then add sodium hydroxide solution and continue to stir and react for 3-5 hours, and after the reaction is completed, cool the reaction product to room temperature, then wash it with distilled water 3-5 times, and then remove the solvent by rotary evaporation to obtain a polyepoxy intermediate;

[0013] Step a4: Add oxidized carbon fiber and acetone to a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 15-25 minutes at an ultrasonic power of 200-300 W. Then, add the polyepoxy intermediate and stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400 r / min for 20-30 minutes. Then, raise the temperature to 60-65°C and continue stirring the reaction for 2-3 hours. After the reaction is completed, cool the reaction product to room temperature, and then vacuum filter it. Place the filter cake in a vacuum drying oven and dry it at a temperature of 60-65°C for 2-3 hours to obtain modified carbon fiber.

[0014] As a further solution of the present invention: the usage ratio of the carbon fiber, concentrated nitric acid and concentrated sulfuric acid in step a1 is 3g:30-40mL:10-15mL.

[0015] As a further solution of the present invention: the carbon fiber in step a1 is polyacrylonitrile-based T300 carbon fiber with an average length of 6 mm and an average diameter of 7 μm.

[0016] As a further solution of the present invention: the mass fraction of the concentrated nitric acid in step a1 is 68%; the mass fraction of the concentrated sulfuric acid is 98%.

[0017] As a further solution of the present invention: the usage ratio of the 3,4-dihydroxybenzaldehyde, anhydrous methanol and 1,3-diamino-2-hydroxypropane solution in step a2 is 20 mmol: 20-25 mL: 10-12 mL.

[0018] As a further solution of the present invention: the 1,3-diamino-2-hydroxypropane solution in step a2 is a solution formed by dissolving 1,3-diamino-2-hydroxypropane in anhydrous methanol at a ratio of 10 mmol:10 mL.

[0019] As a further solution of the present invention: the usage ratio of the polyhydroxy intermediate, benzyltriethylammonium chloride, epichlorohydrin and sodium hydroxide solution in step a3 is 3g:30-35mL:0.1-0.2g:20-25mL.

[0020] As a further solution of the present invention: the mass fraction of the sodium hydroxide solution in step a3 is 20-25%.

[0021] As a further solution of the present invention: the usage ratio of the oxidized carbon fiber, acetone and polyepoxy intermediate in step a4 is 5g:80-100mL:3-17g.

[0022] As a further solution of the present invention: a method for preparing composite aerogel powder by normal pressure method, comprising the following steps:

[0023] Step 1: Weigh 20-25 parts of 4,4'-diaminodiphenyl ether, 30-35 parts of pyromellitic anhydride, 90-100 parts of N-methylpyrrolidone, 5-7 parts of pyridine, 15-21 parts of propionic anhydride, 3-11 parts of 3-aminopropyltriethoxysilane, 6-10 parts of aluminum isopropoxide, 7-11 parts of acetic acid, 18-22 parts of deionized water and 0.5-7.5 parts of modified carbon fiber according to weight parts, and set aside;

[0024] Step 2: Add aluminum isopropoxide, acetic acid and deionized water into a three-necked flask equipped with a stirrer and a thermometer, and stir the mixture for 1-2 hours at a temperature of 25-30° C. and a stirring rate of 300-400 r / min to obtain an alumina sol;

[0025] Step 3: Add 4,4'-diaminodiphenyl ether, isomellitic acid dianhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add pyridine and propionic anhydride and continue to stir and react for 2-3 hours, then add 3-aminopropyltriethoxysilane, alumina sol and modified carbon fiber and continue to stir and react for 1-1.5 hours, then let the gel stand for 20-30 hours, then immerse the gel in anhydrous ethanol for 10-15 hours, then place it in a vacuum drying oven, dry it at normal pressure at a temperature of 50-55°C for 20-30 hours, then heat it to 80-85°C and continue to dry it at normal pressure for 2-3 hours, then crush it to obtain a composite aerogel powder.

[0026] Beneficial effects of the present invention:

[0027] The invention discloses a composite aerogel powder prepared by a normal pressure method and a preparation method thereof. The invention comprises the following steps: stirring aluminum isopropoxide, acetic acid and deionized water to obtain an alumina sol; stirring 4,4'-diaminodiphenyl ether, pyromellitic acid dianhydride and N-methylpyrrolidone to react; then adding pyridine, propionic anhydride, 3-aminopropyltriethoxysilane, alumina sol and modified carbon fiber to continue stirring the reaction; then standing the gel, and immersing the gel in anhydrous ethanol; then drying and crushing the gel at normal pressure to obtain the composite aerogel powder. The composite aerogel powder prepared by the preparation method combines the advantages of alumina aerogel and polyimide aerogel, and the two aerogels are composited to form an interpenetrating network structure. Alumina has a high melting point and high thermal stability, and can withstand high temperature environments without Structural changes occur, and polyimide has excellent mechanical strength. After the two are combined, the two materials can support each other and jointly bear external forces, thereby improving the overall performance of the material. After doping modified carbon fibers into it, it can support the interpenetrating network structure to avoid hole shrinkage, collapse and cracking, further improving the overall stability of the material, giving the composite aerogel powder excellent thermal insulation properties, mechanical properties and high temperature resistance, and is suitable for a variety of high-temperature, low thermal conductivity application scenarios, especially in the fields of aerospace, high-temperature insulation, and thermal insulation materials. It shows significant technical advantages and significantly improves the performance of the product. In addition, the normal pressure method is used to avoid the high temperature and high pressure conditions required for the supercritical drying process. The equipment is simple, the cost is low, and the safety is high, which is conducive to large-scale production.

[0028] In the process of preparing composite aerogel powder, a modified carbon fiber is first prepared. First, the carbon fiber is treated with concentrated nitric acid and concentrated sulfuric acid to remove impurities on the surface of the carbon fiber and introduce a large number of active groups (hydroxyl and carboxyl groups) to obtain oxidized carbon fiber. Then, 3,4-dihydroxybenzaldehyde and 1,3-diamino-2-hydroxypropane are reacted. The aldehyde group on 3,4-dihydroxybenzaldehyde reacts with the amino group on 1,3-diamino-2-hydroxypropane to form a Schiff base structure, forming a polyhydroxy intermediate containing a large number of hydroxyl groups. Then, the polyhydroxy intermediate and epichlorohydrin react. After the ring opening-closing reaction, epichlorohydrin introduces a large number of epoxy groups to the hydroxyl groups of the polyhydroxy intermediate to obtain a polyepoxy intermediate. Finally, the polyepoxy The oxidized carbon fiber is treated with a base intermediate, and the active groups on the oxidized carbon fiber react with the epoxy groups on the polyepoxy intermediate, and a large number of epoxy groups are introduced into the oxidized carbon fiber to obtain modified carbon fiber; the carbon fiber has the advantages of light weight, high strength and high stiffness. After adding it to the composite aerogel powder, the mechanical properties of the composite aerogel powder can be significantly improved, and after the carbon fiber is wrapped by the polyepoxy intermediate, it can be protected, further improving its comprehensive performance, and greatly improving its dispersibility, so that it can be evenly dispersed in the interior of the aerogel powder, and the large number of epoxy groups introduced can be connected to the interior of the composite aerogel powder in the form of chemical bonds, further improving the mechanical properties of the composite aerogel powder. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] This embodiment is a method for preparing composite aerogel powder by normal pressure method, comprising the following steps:

[0032] Step S1: 3 g of polyacrylonitrile-based T300 carbon fiber with an average length of 6 mm and an average diameter of 7 μm, 30 mL of concentrated nitric acid with a mass fraction of 68%, and 10 mL of concentrated sulfuric acid with a mass fraction of 98% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then heated to 85° C. and continued to stir for 2 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven, and dried at a temperature of 60° C. for 2 h to obtain oxidized carbon fiber;

[0033] Step S2: Add 20mmol3,4-dihydroxybenzaldehyde and 20mL of anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 20min at a temperature of 25°C and a stirring rate of 300r / min, then add dropwise 10mL of 1,3-diamino-2-hydroxypropane dissolved in anhydrous methanol at a ratio of 10mmol:10mL while stirring, and control the dropping rate to 1 drop / s. After the dropwise addition is completed, continue to stir and react for 6h under the condition of heating to 60°C. After the reaction is completed, cool the reaction product to room temperature, then pour it into ice water, and then vacuum filter it. Wash the filter cake with distilled water 3 times, then place it in a vacuum drying oven, and dry it at a temperature of 60°C for 2h to obtain a polyhydroxy intermediate;

[0034] Step S3: 3 g of the polyhydroxy intermediate, 30 mL of benzyltriethylammonium chloride and 0.1 g of epichlorohydrin are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture is heated to 90° C. and stirred for reaction for 6 h. Then, 20 mL of a 20% by mass sodium hydroxide solution is added and stirred for reaction for 3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then washed with distilled water 3 times, and then the solvent is removed by rotary evaporation to obtain a polyepoxy intermediate;

[0035] Step S4: 5 g of oxidized carbon fiber and 80 mL of acetone were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated for 15 min at an ultrasonic power of 200 W, then 3 g of a polyepoxy intermediate was added and stirred for 20 min at a temperature of 25 ° C and a stirring rate of 300 r / min, then the temperature was raised to 60 ° C and the stirring reaction was continued for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 60 ° C for 2 h to obtain a modified carbon fiber;

[0036] Step S5: weigh 20 parts of 4,4'-diaminodiphenyl ether, 30 parts of pyromellitic anhydride, 90 parts of N-methylpyrrolidone, 5 parts of pyridine, 15 parts of propionic anhydride, 3 parts of 3-aminopropyltriethoxysilane, 6 parts of aluminum isopropoxide, 7 parts of acetic acid, 18 parts of deionized water and 0.5 parts of modified carbon fiber according to weight parts, and set aside;

[0037] Step S6: adding aluminum isopropoxide, acetic acid and deionized water into a three-necked flask equipped with a stirrer and a thermometer, stirring the mixture for 1 hour at a temperature of 25° C. and a stirring rate of 300 r / min to obtain an alumina sol;

[0038] Step S7: Add 4,4'-diaminodiphenyl ether, isomellitic acid dianhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20 minutes at a temperature of 25°C and a stirring rate of 300r / min, then add pyridine and propionic anhydride and continue to stir and react for 2 hours, then add 3-aminopropyltriethoxysilane, alumina sol and modified carbon fiber and continue to stir and react for 1 hour, then let the gel stand for 20 hours, then immerse the gel in anhydrous ethanol for 10 hours, then place it in a vacuum drying oven, dry it at normal pressure at a temperature of 50°C for 20 hours, then heat it to 80°C and continue to dry it at normal pressure for 2 hours, then crush it to obtain a composite aerogel powder.

[0039] Embodiment 2:

[0040] This embodiment is a method for preparing composite aerogel powder by normal pressure method, comprising the following steps:

[0041] Step S1: 3 g of polyacrylonitrile-based T300 carbon fiber with an average length of 6 mm and an average diameter of 7 μm, 35 mL of concentrated nitric acid with a mass fraction of 68%, and 12 mL of concentrated sulfuric acid with a mass fraction of 98% were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then heated to 88° C. and continued to stir for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, the filter cake was washed with distilled water 4 times, and then placed in a vacuum drying oven, and dried at a temperature of 62° C. for 2.5 h to obtain oxidized carbon fiber;

[0042] Step S2: Add 20mmol3,4-dihydroxybenzaldehyde and 22mL of anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 25min at a temperature of 28°C and a stirring rate of 350r / min, then add 11mL1,3-diamino-2-hydroxypropane dropwise while stirring, wherein the 1,3-diamino-2-hydroxypropane solution formed by dissolving it in anhydrous methanol at a ratio of 10mmol:10mL, and control the dropping rate to 1 drop / s. After the dropwise addition is completed, the temperature is raised to 62°C and the stirring reaction is continued for 7h. After the reaction is completed, the reaction product is cooled to room temperature, then poured into ice water, and then vacuum filtered. The filter cake is washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 62°C for 2.5h to obtain a polyhydroxy intermediate;

[0043] Step S3: 3 g of the polyhydroxy intermediate, 32 mL of benzyltriethylammonium chloride and 0.15 g of epichlorohydrin are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred at 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture is heated to 92° C. and stirred for 7 h. Then, 22 mL of a 22% sodium hydroxide solution is added and stirred for 4 h. After the reaction is completed, the reaction product is cooled to room temperature, and then washed with distilled water 4 times, and then the solvent is removed by rotary evaporation to obtain a polyepoxy intermediate;

[0044] Step S4: 5 g of oxidized carbon fiber and 90 mL of acetone were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated for 20 min at an ultrasonic power of 250 W, then 10 g of a polyepoxy intermediate was added and stirred for 25 min at a temperature of 28 ° C and a stirring rate of 350 r / min, then the temperature was raised to 62 ° C and the stirring reaction was continued for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 62 ° C for 2.5 h to obtain modified carbon fiber;

[0045] Step S5: weigh 22 parts of 4,4'-diaminodiphenyl ether, 32 parts of pyromellitic anhydride, 95 parts of N-methylpyrrolidone, 6 parts of pyridine, 18 parts of propionic anhydride, 7 parts of 3-aminopropyltriethoxysilane, 8 parts of aluminum isopropoxide, 9 parts of acetic acid, 20 parts of deionized water and 4 parts of modified carbon fiber according to weight parts, and set aside;

[0046] Step S6: adding aluminum isopropoxide, acetic acid and deionized water into a three-necked flask equipped with a stirrer and a thermometer, stirring and reacting for 1.5 hours at a temperature of 28° C. and a stirring rate of 350 r / min to obtain an alumina sol;

[0047] Step S7: Add 4,4'-diaminodiphenyl ether, isomellitic acid dianhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 25 minutes at a temperature of 28°C and a stirring rate of 350r / min, then add pyridine and propionic anhydride and continue to stir and react for 2.5 hours, then add 3-aminopropyltriethoxysilane, alumina sol and modified carbon fiber and continue to stir and react for 1.2 hours, then let the gel stand for 25 hours, then immerse the gel in anhydrous ethanol for 12 hours, then place it in a vacuum drying oven, dry it at normal pressure at a temperature of 52°C for 25 hours, then heat it to 82°C and continue to dry it at normal pressure for 2.5 hours, and then crush it to obtain a composite aerogel powder.

[0048] Embodiment 3:

[0049] This embodiment is a method for preparing composite aerogel powder by normal pressure method, comprising the following steps:

[0050] Step S1: 3 g of polyacrylonitrile-based T300 carbon fiber with an average length of 6 mm and an average diameter of 7 μm, 40 mL of concentrated nitric acid with a mass fraction of 68%, and 15 mL of concentrated sulfuric acid with a mass fraction of 98% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then heated to 90° C. and continued to stir for reaction for 3 h. After the reaction, the reaction product is cooled to room temperature, and then vacuum filtered, the filter cake is washed with distilled water 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 65° C. for 3 h to obtain oxidized carbon fiber;

[0051] Step S2: Add 20mmol3,4-dihydroxybenzaldehyde and 25mL anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 30min at a temperature of 30°C and a stirring rate of 400r / min, then add 12mL1,3-diamino-2-hydroxypropane dropwise while stirring, wherein the 1,3-diamino-2-hydroxypropane solution formed by dissolving it in anhydrous methanol at a ratio of 10mmol:10mL, and control the dropping rate to 2 drops / s. After the dropwise addition is completed, the temperature is raised to 65°C and the stirring reaction is continued for 8h. After the reaction is completed, the reaction product is cooled to room temperature, then poured into ice water, and then vacuum filtered. The filter cake is washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 65°C for 3h to obtain a polyhydroxy intermediate;

[0052] Step S3: 3 g of the polyhydroxy intermediate, 35 mL of benzyltriethylammonium chloride and 0.2 g of epichlorohydrin are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 95° C. and stirred for reaction for 8 h. Then, 25 mL of a 25% by mass sodium hydroxide solution is added and stirred for reaction for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then washed with distilled water 5 times, and then the solvent is removed by rotary evaporation to obtain a polyepoxy intermediate;

[0053] Step S4: 5 g of oxidized carbon fiber and 100 mL of acetone were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated for 25 min at an ultrasonic power of 300 W, then 17 g of a polyepoxy intermediate was added and stirred for 30 min at a temperature of 30 ° C and a stirring rate of 400 r / min, then the temperature was raised to 65 ° C and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 65 ° C for 3 h to obtain modified carbon fiber;

[0054] Step S5: weigh 25 parts of 4,4'-diaminodiphenyl ether, 35 parts of pyromellitic anhydride, 100 parts of N-methylpyrrolidone, 7 parts of pyridine, 21 parts of propionic anhydride, 11 parts of 3-aminopropyltriethoxysilane, 10 parts of aluminum isopropoxide, 11 parts of acetic acid, 22 parts of deionized water and 7.5 parts of modified carbon fiber according to weight parts, and set aside;

[0055] Step S6: adding aluminum isopropoxide, acetic acid and deionized water into a three-necked flask equipped with a stirrer and a thermometer, stirring and reacting for 2 hours at a temperature of 30° C. and a stirring rate of 400 r / min to obtain an alumina sol;

[0056] Step S7: Add 4,4'-diaminodiphenyl ether, isomellitic acid dianhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, and stir the reaction for 30 minutes at a temperature of 30°C and a stirring rate of 400r / min. Then, add pyridine and propionic anhydride and continue to stir the reaction for 3 hours. Then, add 3-aminopropyltriethoxysilane, alumina sol and modified carbon fiber and continue to stir the reaction for 1.5 hours. Then, let the gel stand for 30 hours. Then, immerse the gel in anhydrous ethanol for 15 hours, and then place it in a vacuum drying oven. Dry it at normal pressure at a temperature of 55°C for 30 hours, then heat it to 85°C and continue to dry it at normal pressure for 3 hours. Then, crush it to obtain a composite aerogel powder.

[0057] Comparative Example 1:

[0058] This comparative example is a method for preparing composite aerogel powder by normal pressure method, comprising the following steps:

[0059] Step S1: weigh 25 parts of 4,4'-diaminodiphenyl ether, 35 parts of pyromellitic anhydride, 100 parts of N-methylpyrrolidone, 7 parts of pyridine, 21 parts of propionic anhydride and 11 parts of 3-aminopropyltriethoxysilane according to weight parts, and set aside;

[0060] Step S2: Add 4,4'-diaminodiphenyl ether, pyromellitic anhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, and stir the reaction for 30 minutes at a temperature of 30°C and a stirring rate of 400r / min. Then, add pyridine and propionic anhydride and continue to stir the reaction for 3 hours. Then, add 3-aminopropyltriethoxysilane and continue to stir the reaction for 1.5 hours. Then, let the gel stand for 30 hours. Then, immerse the gel in anhydrous ethanol for 15 hours, and then place it in a vacuum drying oven. Dry it at normal pressure at a temperature of 55°C for 30 hours, then heat it to 85°C and continue to dry it at normal pressure for 3 hours. Then, crush it to obtain a composite aerogel powder.

[0061] Comparative Example 2:

[0062] This comparative example is a method for preparing composite aerogel powder by normal pressure method, comprising the following steps:

[0063] Step S1: weigh 25 parts of 4,4'-diaminodiphenyl ether, 35 parts of pyromellitic anhydride, 100 parts of N-methylpyrrolidone, 7 parts of pyridine, 21 parts of propionic anhydride, 11 parts of 3-aminopropyltriethoxysilane, 10 parts of aluminum isopropoxide, 11 parts of acetic acid and 22 parts of deionized water according to weight parts, and set aside;

[0064] Step S2: adding aluminum isopropoxide, acetic acid and deionized water into a three-necked flask equipped with a stirrer and a thermometer, stirring and reacting for 2 hours at a temperature of 30° C. and a stirring rate of 400 r / min to obtain an alumina sol;

[0065] Step S3: Add 4,4'-diaminodiphenyl ether, isomellitic anhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, and stir the reaction for 30 minutes at a temperature of 30°C and a stirring rate of 400r / min. Then, add pyridine and propionic anhydride and continue to stir the reaction for 3 hours. Then, add 3-aminopropyltriethoxysilane and alumina sol and continue to stir the reaction for 1.5 hours. Then, let the gel stand for 30 hours. Then, immerse the gel in anhydrous ethanol for 15 hours, and then place it in a vacuum drying oven. Dry it at normal pressure at a temperature of 55°C for 30 hours, then heat it to 85°C and continue to dry it at normal pressure for 3 hours. Then, crush it to obtain a composite aerogel powder.

[0066] Comparative Example 3:

[0067] This comparative example is a method for preparing composite aerogel powder by normal pressure method, comprising the following steps:

[0068] Step S1: 3 g of polyacrylonitrile-based T300 carbon fiber with an average length of 6 mm and an average diameter of 7 μm, 40 mL of concentrated nitric acid with a mass fraction of 68%, and 15 mL of concentrated sulfuric acid with a mass fraction of 98% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then heated to 90° C. and continued to stir for reaction for 3 h. After the reaction, the reaction product is cooled to room temperature, and then vacuum filtered, the filter cake is washed with distilled water 5 times, and then placed in a vacuum drying oven, and dried at a temperature of 65° C. for 3 h to obtain oxidized carbon fiber;

[0069] Step S2: Add 20mmol3,4-dihydroxybenzaldehyde and 25mL anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 30min at a temperature of 30°C and a stirring rate of 400r / min, then add 12mL1,3-diamino-2-hydroxypropane dropwise while stirring, wherein the 1,3-diamino-2-hydroxypropane solution formed by dissolving it in anhydrous methanol at a ratio of 10mmol:10mL, and control the dropping rate to 2 drops / s. After the dropwise addition is completed, the temperature is raised to 65°C and the stirring reaction is continued for 8h. After the reaction is completed, the reaction product is cooled to room temperature, then poured into ice water, and then vacuum filtered. The filter cake is washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 65°C for 3h to obtain a polyhydroxy intermediate;

[0070] Step S3: 3 g of the polyhydroxy intermediate, 35 mL of benzyltriethylammonium chloride and 0.2 g of epichlorohydrin are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 95° C. and stirred for reaction for 8 h. Then, 25 mL of a 25% by mass sodium hydroxide solution is added and stirred for reaction for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then washed with distilled water 5 times, and then the solvent is removed by rotary evaporation to obtain a polyepoxy intermediate;

[0071] Step S4: 5 g of oxidized carbon fiber and 100 mL of acetone were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically treated for 25 min at an ultrasonic power of 300 W, then 17 g of a polyepoxy intermediate was added and stirred for 30 min at a temperature of 30 ° C and a stirring rate of 400 r / min, then the temperature was raised to 65 ° C and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 65 ° C for 3 h to obtain modified carbon fiber;

[0072] Step S5: weigh 25 parts of 4,4'-diaminodiphenyl ether, 35 parts of pyromellitic anhydride, 100 parts of N-methylpyrrolidone, 7 parts of pyridine, 21 parts of propionic anhydride, 11 parts of 3-aminopropyltriethoxysilane and 7.5 parts of modified carbon fiber according to weight parts, and set aside;

[0073] Step S6: Add 4,4'-diaminodiphenyl ether, isomellitic anhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, and stir the reaction for 30 minutes at a temperature of 30°C and a stirring rate of 400r / min. Then, add pyridine and propionic anhydride and continue to stir the reaction for 3 hours. Then, add 3-aminopropyltriethoxysilane and modified carbon fiber and continue to stir the reaction for 1.5 hours. Then, let the gel stand for 30 hours. Then, immerse the gel in anhydrous ethanol for 15 hours, and then place it in a vacuum drying oven. Dry it at normal pressure at a temperature of 55°C for 30 hours, then heat it to 85°C and continue to dry it at normal pressure for 3 hours. Then, crush it to obtain a composite aerogel powder.

[0074] Comparative Example 4:

[0075] This comparative example is a method for preparing composite aerogel powder by normal pressure method, comprising the following steps:

[0076] Step S1: weigh 25 parts of 4,4'-diaminodiphenyl ether, 35 parts of pyromellitic anhydride, 100 parts of N-methylpyrrolidone, 7 parts of pyridine, 21 parts of propionic anhydride, 11 parts of 3-aminopropyltriethoxysilane, 10 parts of aluminum isopropoxide, 11 parts of acetic acid, 22 parts of deionized water and 7.5 parts of polyacrylonitrile-based T300 carbon fiber with an average length of 6 mm and an average diameter of 7 μm, according to weight parts, and set aside;

[0077] Step S2: adding aluminum isopropoxide, acetic acid and deionized water into a three-necked flask equipped with a stirrer and a thermometer, stirring and reacting for 2 hours at a temperature of 30° C. and a stirring rate of 400 r / min to obtain an alumina sol;

[0078] Step S3: Add 4,4'-diaminodiphenyl ether, isomellitic anhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 30 minutes at a temperature of 30°C and a stirring rate of 400r / min, then add pyridine and propionic anhydride and continue to stir and react for 3 hours, then add 3-aminopropyltriethoxysilane, alumina sol and polyacrylonitrile-based T300 carbon fiber with an average length of 6mm and an average diameter of 7μm and continue to stir and react for 1.5 hours, then let the gel stand for 30 hours, then immerse the gel in anhydrous ethanol for 15 hours, then place it in a vacuum drying oven, dry it at normal pressure at a temperature of 55°C for 30 hours, then heat it to 85°C and continue to dry it at normal pressure for 3 hours, then crush it to obtain a composite aerogel powder.

[0079] The composite aerogel powders in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the test results are shown in the following table:

[0080] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be known that the composite aerogel powder of the present application has excellent thermal insulation performance, mechanical properties and high temperature resistance.

[0081] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0082] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined in this application, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing composite aerogel powder by a normal pressure method, characterized in that: It includes the following components by weight: 20-25 parts of 4,4'-diaminodiphenyl ether, 30-35 parts of pyromellitic anhydride, 90-100 parts of N-methylpyrrolidone, 5-7 parts of pyridine, 15-21 parts of propionic anhydride, 3-11 parts of 3-aminopropyltriethoxysilane, 6-10 parts of aluminum isopropoxide, 7-11 parts of acetic acid, 18-22 parts of deionized water and 0.5-7.5 parts of modified carbon fiber; Wherein, the modified carbon fiber is prepared by the following steps: Step a1: stirring carbon fiber, concentrated nitric acid and concentrated sulfuric acid to react, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing and drying the filter cake to obtain oxidized carbon fiber; Step a2: 3,4-dihydroxybenzaldehyde and anhydrous methanol are stirred for reaction, and then 1,3-diamino-2-hydroxypropane solution is added dropwise while stirring. After the addition is completed, the stirring reaction is continued. After the reaction is completed, the reaction product is cooled and then poured into ice water. After vacuum filtration, the filter cake is washed and dried to obtain a polyhydroxy intermediate; Step a3: stirring the polyhydroxy intermediate, benzyltriethylammonium chloride and epichlorohydrin to react, then adding sodium hydroxide solution and continuing stirring the reaction, cooling the reaction product after the reaction is completed, then washing it, and then rotary evaporating it to obtain a polyepoxy intermediate; Step a4: subjecting the oxidized carbon fiber and acetone to ultrasonic treatment, and then adding the polyepoxy intermediate to carry out stirring reaction. After the reaction is completed, the reaction product is cooled, and then vacuum filtered, and the filter cake is dried to obtain modified carbon fiber.

2. The composite aerogel powder prepared by a normal pressure method according to claim 1, characterized in that: The usage ratio of the carbon fiber, concentrated nitric acid and concentrated sulfuric acid in step a1 is 3g:30-40mL:10-15mL.

3. The composite aerogel powder prepared by the normal pressure method according to claim 1, characterized in that: The carbon fiber in step a1 is polyacrylonitrile-based T300 carbon fiber with an average length of 6 mm and an average diameter of 7 μm.

4. The method for preparing composite aerogel powder by a normal pressure method according to claim 1, characterized in that: The mass fraction of the concentrated nitric acid in step a1 is 68%; the mass fraction of the concentrated sulfuric acid is 98%.

5. The method for preparing composite aerogel powder by normal pressure method according to claim 1, characterized in that: The usage ratio of the 3,4-dihydroxybenzaldehyde, anhydrous methanol and 1,3-diamino-2-hydroxypropane solution in step a2 is 20 mmol: 20-25 mL: 10-12 mL.

6. The composite aerogel powder prepared by the normal pressure method according to claim 1, characterized in that: The 1,3-diamino-2-hydroxypropane solution in step a2 is a solution formed by dissolving 1,3-diamino-2-hydroxypropane in anhydrous methanol at a ratio of 10 mmol:10 mL.

7. The composite aerogel powder prepared by the normal pressure method according to claim 1, characterized in that: The usage ratio of the polyhydroxy intermediate, benzyltriethylammonium chloride, epichlorohydrin and sodium hydroxide solution in step a3 is 3g:30-35mL:0.1-0.2g:20-25mL.

8. The method for preparing composite aerogel powder by normal pressure method according to claim 1, characterized in that: The mass fraction of the sodium hydroxide solution in step a3 is 20-25%.

9. The method for preparing composite aerogel powder by normal pressure method according to claim 1, characterized in that: The usage ratio of the oxidized carbon fiber, acetone and polyepoxy intermediate in step a4 is 5g:80-100mL:3-17g.

10. A method for preparing composite aerogel powder by normal pressure method according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Weigh 20-25 parts of 4,4'-diaminodiphenyl ether, 30-35 parts of pyromellitic anhydride, 90-100 parts of N-methylpyrrolidone, 5-7 parts of pyridine, 15-21 parts of propionic anhydride, 3-11 parts of 3-aminopropyltriethoxysilane, 6-10 parts of aluminum isopropoxide, 7-11 parts of acetic acid, 18-22 parts of deionized water and 0.5-7.5 parts of modified carbon fiber according to weight parts, and set aside; Step 2: Add aluminum isopropoxide, acetic acid and deionized water into a three-necked flask equipped with a stirrer and a thermometer, and stir the mixture for 1-2 hours at a temperature of 25-30° C. and a stirring rate of 300-400 r / min to obtain an alumina sol; Step 3: Add 4,4'-diaminodiphenyl ether, isomellitic acid dianhydride and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add pyridine and propionic anhydride and continue to stir and react for 2-3 hours, then add 3-aminopropyltriethoxysilane, alumina sol and modified carbon fiber and continue to stir and react for 1-1.5 hours, then let the gel stand for 20-30 hours, then immerse the gel in anhydrous ethanol for 10-15 hours, then place it in a vacuum drying oven, dry it at normal pressure at a temperature of 50-55°C for 20-30 hours, then heat it to 80-85°C and continue to dry it at normal pressure for 2-3 hours, then crush it to obtain a composite aerogel powder.

Citation Information

Patent Citations

  • Interface-modified carbon fiber / epoxy resin-based composite material and preparation method thereof

    CN112521644A

  • Preparation method of high-temperature-resistant silicon-modified alumina aerogel

    CN113683110A

  • Heat preservation and insulation coating for battery box of electric aircraft and preparation method of heat preservation and insulation coating

    CN117264538A

  • High-temperature-resistant polyimide aerogel composite material as well as preparation method and application thereof

    CN118909301A

  • Method for surface treating fine carbon fiber and coated fine carbon fiber produced by the method

    JP2010248660A